The Impact of Quality Management Systems of Selected Businesses in Caraga Region, Philippines - Gary Cris R. Pelegrino; Emilio D. Matheu Jr. (RIRAI Publisher, 2026)
This research intended to study the impact of quality management systems (QMS) of selected businesses in the Caraga Region, Philippines. Specifically, it sought to determine the effect of QMS in terms of customer focus, leadership, engagement of people, and process improvement, as well as assess significant differences in respondents' evaluations based on company and position. Additionally, the study aimed to propose improvements based on the findings. Using the descriptive survey method, a researcher-made questionnaire was employed for data collection, supplemented by online interviews and focus group discussions (FGDs). Key findings revealed that QMS had a great effect on customer focus, leadership, and engagement of people, while process improvement showed a very great effect. Statistical analysis using Friedman’s test indicated no significant difference in responses between companies, but ANOVA tests revealed significant differences across all areas when grouped by position (management, part-time, and regular full-time employees).